The Political Setting of Social Security Contributions in Europe in the Business Cycle - Toralf Pusch; Ingmar Kumpmann (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2011)
Social security revenues are influenced by business cycle movements. In order to support the working of automatic stabilizers it would be necessary to calculate social insurance contribution rates independently from the state of the business cycle. This paper investigates whether European countries set social contribution rates according to such a rule. By means of VAR estimations, country-specific effects can be analyzed - in contrast to earlier studies which used a panel design. As a result, some countries under investigation seem to vary their social contribution rates in a procyclical way. – – Die Einnahmen der Sozialversicherung unterliegen dem Einfluss des Konjunkturzyklus. Soll die Beitragserhebung der Sozialversicherung nicht prozyklisch schwanken, muss die Höhe der Beitragssätze zyklusübergreifend festgelegt werden. Diese Arbeit geht der Frage nach, ob die Änderungen der Beitragssätze zur Sozialversicherung in europäischen Ländern diesem Grundsatz folgen oder im Gegensatz dazu in Abhängigkeit von der jeweils aktuellen Wirtschaftslage festgelegt werden. Mit Hilfe von VAR-Schätzungen werden dabei - anders als in bisherigen Panel-Studien - die Zusammenhänge länderspezifisch erforscht. Ergebnis der Studie ist, dass einige Länder ihre Sozialversicherungsbeiträge prozyklisch anpassen.
urn:nbn:de:101:1-201103183383
Keywords: E62; H53; H55; H75; J32; 330; Welfare state; procyclical policy; automatic stabilizers; social insurance; fiscal policy; European Union; business cycle; Sozialstaat; Konjunkturpolitik; automatische Stabilisatoren; Sozialversicherung; Finanzpolitik; Europäische Union; Konjunkturzyklus